Turnover de professores na região oeste do Paraná e suas influências nos resultados da avaliação em larga escala (Prova Brasil/ SAEB) – 2015-2021 - Nogueira, Arcielli Royer (2021)
Turnover is a problem that affects institutions, generating a large inflow and outflow of professionals. In this research, we seek to understand how teacher turnover occurs in the western region of Paraná (in municipalities belonging to AMOP) and how it can influence the results of the Prova Brasil, considering that it is an increasingly present reality in public schools at different levels of education. The intention is to understand the problem situation how teacher turnover influences and impacts the results of the large-scale assessment (Prova Brasil). Thus, the objective is to research and analyze teacher turnover data in the western region of Paraná, to understand whether there is an influence on IDEB results in the final years of elementary school I (5th year), with teacher turnover. By focusing, this article is qualitative and quantitative, with bibliographical, documental, and content analysis research. The results show that most municipalities in western Paraná have teachers on a temporary contract. This leads to high levels of turnover, which reflect in the results of Prova Brasil.